Hand function in children with unilateral spastic cerebral palsy - Feriha Hadžagić Ćatibušić; Sajra Užičanin; Deniz Bulja; Emira Gasal Gvozdenović (Medicinski glasnik, 2018)
Aim: To assess hand function and explore the relationship between hand function and neuroimaging findings in children with unilateral spastic cerebral palsy (US CP). Methods: Hand function was assessed using Manual Ability Classification System (MACS, I-V). Brain lesions were divided into five groups: brain maldevelopment (MAL), periventricular white matter lesions (PV WM), cortical/subcortical gray matter lesions (C/SC GM), nonspecific and normal findings. Results: Of 114 children with US CP (77 boys and 37 girls), 56 were with right-sided and 58 with left-sided involvement. MACS I was found in 49 (42.9%), MACS II in 19 (16.7%), MACS III in 19 (16.7 %), MACS IV in 9 (7.9%) and MACS V in 18 (15.8%) children (p=0.002). Computed tomography (CT) as the only neuroimaging has been done in 18 (15.8%), magnetic resonance imaging (MRI) at 94 (82.5%) children, whereas 2 (1.7%) children had neither CT nor MRI. The CT showed PV WM in eight (44.4%), C/SC GM lesions in six (33.3%), and normal findings in four (22.2%) children (p=0.709). The MRI showed MAL in eight (8.5%), PV WM in 46 (48.9%), C/SC GM in 28 (29.8%), miscellaneous in two (2.1%), and normal finding in 10 (10.7%) children (p=0.0001). Mild hand dysfunction (MACS I and II) was assessed in 68 (59.7%) children, of which 33 had PV WM lesions (p=0.001). Conclusion: Mild hand dysfunction in children with US CP has been significantly associated with PV WM lesions. The type of brain lesion may help to identify its timing and predict the level of hand dysfunction.
Keywords: cerebral palsy; child; neuroimaging